2019
DOI: 10.7717/peerj.6288
|View full text |Cite
|
Sign up to set email alerts
|

Convergent origin of the narrowly lanceolate leaf in the genus Aster—with special reference to an unexpected discovery of a new Aster species from East China

Abstract: Narrowly lanceolate leaves occur frequently in the genus Aster. It was often employed as a distinguishing character in the taxonomy of this genus. The origin of this particular leaf shape, however, has never been investigated using comparative methods. In this study, we reconstructed a comprehensive phylogeny that includes most species of Aster with narrowly lanceolate leaf. We then gathered data on riparian habitats and the presence or absence of narrowly lanceolate leaves, and investigated the evolutionary a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 31 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…Aster quanzhouensis is known only from two populations (Dehua and Yongchun counties) restricted to Quanzhou, Fujian, China, while A. tonglingensis is restricted to Mt. Tongling Natural Reserve, Wencheng county, Zhejiang (Zhang et al 2019). These two species occupy the same ecological conditions, but are geographically separated by a distance of 400 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aster quanzhouensis is known only from two populations (Dehua and Yongchun counties) restricted to Quanzhou, Fujian, China, while A. tonglingensis is restricted to Mt. Tongling Natural Reserve, Wencheng county, Zhejiang (Zhang et al 2019). These two species occupy the same ecological conditions, but are geographically separated by a distance of 400 km.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of Aster quanzhouensis and A. tonglingensis. The data of the latter species were taken fromZhang et al (2019).…”
mentioning
confidence: 99%
“…Nuclear ribosomal ITS and ETS sequences of 66 taxa, representing major clades of the genus Aster and its relatives (Li et al 2012, 2017, 2020, Zhang et al 2015, 2019, Xiao et al 2019a, b2019b), were downloaded from GenBank (Supporting information). Additionally, six newly sequenced accessions included two samples of the new taxon (Supporting information).…”
Section: Methodsmentioning
confidence: 99%
“…China has over 123 accepted names of Aster (Chen et al 2011) and its southwest region is the distribution centre of this genus (Li et al 2012). In China, eight new Aster species have been described the last five years (Zhang et al 2015, 2019, Li et al 2017, 2020, Xiao et al 2019a, b2019b, 2020, Xiong et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on combined sequences of ITS, ETS, and trnL-F , the recent phylogenetic tree demonstrated that A. pekinensis was sister to A. indicus (Zhang et al. 2019 ). In this study, we reported the complete plastome of A. pekinensis , which will be helpful for species identification and the phylogenetic analysis of the genus Aster .…”
mentioning
confidence: 99%